Comparison of the Effect of Some Essential Oils on the Growth of Penicillium verrucosum and its Ochratoxin a Production - Ozcakmak, Sibel; Gul, Osman; Dervisoglu, Muhammet; Yilmaz, Azime; Sagdic, Osman; Arici, Muhammet (WILEY, 2017)
Antifungal activities of four essential oils from mint, garlic, sage and wild oregano were evaluated against ochratoxigenic Penicillium verrucosum incubated at different times. The fungal mycelium growth was completely inhibited (fungicidal effect) at concentrations of 0.5 and 0.25% of the garlic and wild oregano essential oils. However, concentrations of 0.125 and 0.065% of essential oils were showed the low reductions to be 37.05-46.59 and 35.68-45.51%, respectively. Sage essential oil showed the lowest antifungal activity. In addition, these essential oils were evaluated for their potential to control ochratoxin A produced by P. verrucosum. Ochratoxin A production could be significantly reduced by sage and mint essential oils and completely prevented by garlic and wild oregano essential oils at the concentrations of 0.5 and 0.25%. The results of this study revealed that garlic and wild oregano essential oils could be used as a food preservative against the fungal contamination and its toxin production. Practical ApplicationThe contamination of molds and mycotoxins in food and feedstuff is still the most important issues facing the food industry and consumers. Today, essential oils have been found common use for the inhibition of fungal growth and mycotoxin production. However, there is no enough knowledge about the using most effective essential oils for Penicillium verrucosum inactivation. In the present study, antifungal activities of four essential oils with different concentrations were investigated and garlic and wild oregano essential oils could be used for inhibition of P. verrucosum growth and its ochratoxin A production.
Keywords: ANTIFUNGAL ACTIVITY; IN-VITRO; ANTIMICROBIAL ACTIVITY; CHEMICAL-COMPOSITION; ASPERGILLUS-FLAVUS; FUNGI; L.; ANTIOXIDANT; EXTRACTS; THYME; Food Science & Technology